Improving the Life of Former Female Migrant Domestic Workers - Rosita Tandos (Asian Social Work Journal, 2018)
Some studies exploring the life of migrant domestic workers found that the main factor that push Indonesian migrant domestic workers is experiencing severe economic condition (Raharto, 2000; Silvey, 2004; Pitoyo, 2007). The poor economic condition forces women and girls to be domestic workers. Additionally, cultural value of patriarchy puts a responsibility for women at domestic area influencing the women’s ability to fill the demand of the domestic workers in overseas. This paper addresses the main topic of enhancing protection and empowerment for Indonesian female migrant domestic workers by specifically exploring the issues after working in overseas. The study exploring the life of former migrant domestic workers from Bondan village of Indramayu district using qualitative method. The informants of the study were the workers who just finished their work contract, staying at the moment in the village waiting for the next call or deciding to stop working in overseas. The number of participants was 40 women (n=40), joining focus-group discussions and in-depth interviews. The theoretical frameworks used in the study consist of human capabilities approach, feminist perspective, and social work theories of empowering individual, family, and community. Then, the discussion covers three main points: first, discussion of the theories applied in the study; second, the life of transnational domestic workers of examining abusive conditions; third, developing future practices to empowering the workers; and fourth, a part of the paper provides conclusion to whole points discussed.